Nativus gen. nov., a new huntsman spider genus from South America (Araneae: Sparassidae: Heteropodinae) - Casas, Cristian M.; Rheims, Cristina A. (Zootaxa, 2023)
In this paper, the new genus, Nativus gen. nov. is proposed to include the type species, Nativus tupana sp. nov. (♂♀) from Brazil and nine new species: N. carare sp. nov. (♂), N. hazzii sp. nov. (♂♀), N. janai sp. nov. (♂), N. nocaima sp. nov. (♂♀), N. tawu sp. nov. (♂♀) and N. yurupari sp. nov. (♂♀) from Colombia, N. juruti sp. nov. (♂) and N. mariua sp. nov. (♂♀) from Brazil, and N. napo sp. nov. (♂♀) from Peru. The genus is placed in the subfamily Heteropodinae due to the presence of intermarginal denticles on the chelicerae, a long-toothed female palpal claw, two recurved eye rows with median eyes smaller than laterals, and only one lateral spine on each side of metatarsi I−II, as well as a ventral branch on the RTA (vRTA) in the male palp. Within Heteropodinae, it seems to be more closely related to Guadana Rheims and Sparianthina Banks due to the presence of intermarginal denticles along the entire cheliceral groove and a dorsal tegular apophysis (DTA) in the male palp. All species are described and illustrated. An identification key and distribution maps are provided for all species of the genus.